Exposure of Histone Deacetylase-2 Inhibitor Curcumin and Its Analogues in Self-Nano Emulsifying Drug Delivery System Change Memory and Cognitive Function, Anxiety, and Social Interaction Behavior in Mouse - Nunung Yuniarti; Febri Wulandari; Ulfah Laily Azizah; Yance Anas; Retno Murwanti (Sanata Dharma University, 2024)
Class 1 and 2 histone deacetylase inhibitors (HDACI) have been reported as novel therapeutic approaches to treat neurodegenerative disorders, depression, anxiety, and cognitive deficits. HDACI ameliorated deficits in cognition and stress-related behaviors in a wide range of neurologic and psychiatric disorders. Preclinically, behavioral bioassay can be used to predict the influence of new compounds for treatment of these illnesses. Curcumin and its new analogues PGV-0 and PGV-1 have been reported to inhibit HDAC2. However, reports regarding the effect of curcumin and its analogues on memory and cognitive function, anxiety, and social interaction behavior are as yet to be examined. Mice were divided into control and treated groups. Brain disorder was induced by oral administration of 10% ethanol in sodium-CMC for 7 days. Curcumin, PGV-0, PGV-1, and sodium butyrate (as positive control) were then given orally once a day for 21 days. The behavior tests of social interaction, open field, radial 8-arm-maze, and passive avoidance were performed on day 29. To increase dissolution and bioavailability of the compounds, they were formulated in a self-nano emulsifying drug delivery system (SNEDDS). Brains were isolated and analyzed using PCR to investigate the expression of genes related to neurobehavioral disorders hdac2, trkB, and bdnf. In different doses, curcumin, PGV-0, and PGV-1 increased social interaction capability, declined anxiety level, and improved long-term memory and cognitive function. The mechanism proposed is: HDACI curcumin and its analogues (PGV-0 and PGV-1) that keep the histone protein in acetylation state increase bdnf expression. The increased trkB expression is increasing the activation of the bdnf gene because trkB is the primary receptor of bdnf that supports the survival of existing neurons and encourages the growth and differentiation of new neurons and synapses. Thus, those mechanisms could improve long-term memory and cognitive function, increase social interaction, and reduce anxiety in ethanol-induced mice with brain disorders.